2024
DOI: 10.1029/2023gl106840
|View full text |Cite
|
Sign up to set email alerts
|

Observations Reveal Intense Air‐Sea Exchanges Over Submesoscale Ocean Front

Haiyuan Yang,
Zhaohui Chen,
Shantong Sun
et al.

Abstract: Air‐sea exchanges across oceanic fronts are critical in powering cloud formation, precipitation, and atmospheric storms. Oceanic submesoscale fronts of scales 1–10 km are characterized by strong sea surface temperature (SST) gradients. However, it remains elusive how submesoscale fronts affect the overlying atmosphere due to a lack of high‐resolution observations or models. Based on rare high‐resolution in situ observations in the Kuroshio Extension region, we quantify the air‐sea exchanges across an oceanic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The mesoscale SST-wind coupling processes have been relatively extensively investigated in previous studies (see reviews by R. D. Small et al (2008); Seo et al (2023)), but the smallscale oceanic forcing (below the deformation radius) on the MABL processes is only beginning to be investigated (Czaja et al, 2019). Recently, both observations (Acquistapace et al, 2022;de Szoeke et al, 2021;Gaube et al, 2019;Iyer et al, 2022;Shao et al, 2019;Yang et al, 2024) and simulations (Conejero et al, 2024;Strobach et al, 2022;Sullivan & McWilliams, 2022;Sullivan et al, 2020;Wenegrat & Arthur, 2018) have shown that submesoscale SST variability can have direct impacts on the MABL, including surface wind speed, air-sea heat flux, and cloud formation (Acquistapace et al, 2022). The energetic submesoscale processes in the Southern Ocean also implied the strong submesoscale air-sea coupling (Siegelman et al, 2020;Su et al, 2018;Swart et al, 2023), but it remains largely unexplored, particularly from the observation perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The mesoscale SST-wind coupling processes have been relatively extensively investigated in previous studies (see reviews by R. D. Small et al (2008); Seo et al (2023)), but the smallscale oceanic forcing (below the deformation radius) on the MABL processes is only beginning to be investigated (Czaja et al, 2019). Recently, both observations (Acquistapace et al, 2022;de Szoeke et al, 2021;Gaube et al, 2019;Iyer et al, 2022;Shao et al, 2019;Yang et al, 2024) and simulations (Conejero et al, 2024;Strobach et al, 2022;Sullivan & McWilliams, 2022;Sullivan et al, 2020;Wenegrat & Arthur, 2018) have shown that submesoscale SST variability can have direct impacts on the MABL, including surface wind speed, air-sea heat flux, and cloud formation (Acquistapace et al, 2022). The energetic submesoscale processes in the Southern Ocean also implied the strong submesoscale air-sea coupling (Siegelman et al, 2020;Su et al, 2018;Swart et al, 2023), but it remains largely unexplored, particularly from the observation perspective.…”
Section: Introductionmentioning
confidence: 99%